Planificación de un sistema de gestión de calidad basado en la NTC ISO 9001:2015 en una empresa de servicios de ingeniería (2019)
The objective of this monograph is to plan a quality management system in an engineering services company. To achieve this proposal, it was structured in a framework where the bases are located, as well as the references for this monograph. Initially a diagnosis is made, where the current state of the company is identified against the criteria of the standard by means of a checklist instrument.